Broadband Transformation Acoustic Waveguide With Anisotropic Density Based on Pentamode Metamaterials - Chen, Xing; Cai, Li; Wen, Jihong (Frontiers in Materials, 2022)
Multiple layer anisotropic fluid medium is critical to the realization of transformation acoustic devices, such as cloak or bend waveguide. Pentamode metamaterials have attracted extensive attention as a solid artificial version with anisotropic modulus to approximate liquids. In this paper, we present an approach to realize fluid-like anisotropic density by using pentamode materials, and an underwater bend acoustic waveguides with anisotropic density is designed and fabricated to demonstrate the effectiveness of it. Simulation results indicate that, compared with anisotropic-modulus design by using pentamode materials, wider bandwidth acoustic modulation effect can be obtained. An in-depth and comprehensive analysis of the mechanisms of the broadband characteristics is provided by calculating the band structure of the pentamode metamaterials constituting the acoustic waveguides and analyzing their vibration modes. Finally, remarkable wavefront manipulation for underwater acoustics based on the acoustic waveguide with anisotropic density is experimentally verified.